Evaluation of seismic site amplification factors in Yogyakarta using One-Dimensional site response analysis - Marasabessy, Muhammad Irfan; Saputra, Elvis; Basarah, Yuamar I (Teknisia, 2025)
This study evaluates seismic site amplification in Yogyakarta using one-dimensional (1D) nonlinear site response analysis. Subsurface conditions were characterized using borehole and Standard Penetration Test (SPT) data from four different locations. Ground motion records were selected and matched to the seismic hazard target spectrum at the bedrock level in Yogyakarta. The nonlinear site response analysis was then used to propagate the seismic waves to the ground surface using the DEEPSOIL program. The results show de-amplification at short periods (T < 0.5 s) and amplification at longer periods (T > 1 s), The highest amplification is observed at T = 0.15 s, with an average factor of 3.47. A comparison with the Indonesian seismic design code SNI 1726:2019, which shows that the code provides more conservative estimates than the site-specific analysis in this study. The analysis also shows that lower input motion intensity at bedrock (PGA = 0.02g) leads to higher amplification, while higher PGA (up to 0.72g) results in reduced response. This study highlights the need for site-specific analysis and consideration of input motion variability.